Еlectrophysical properties of carbon nanotubes/NiCo composites - O. M. Lisova; S. M. Makhno; G. M. Gunya; P. P. Gorbyk (Хімія, фізика та технологія поверхні)
Metal-containing nanocomposites containing nanoparticles of organic and inorganic materials, attract considerable attention of specialists in recent years due to a large number of possible applications.